S-54-5: CHANGES IN ESTIMATED SALT AND POTASSIUM INTAKE AND SODIUM-TO-POTASSIUM RATIO USING SPOT URINE MEASUREMENTS: A 10-YEAR FOLLOW-UP OF NIPPON DATA2010. (January 2023) - Kitaoka, Kaori; Kadota, Aya; Okami, Yukiko; Kondo, Keiko; Harada, Akiko; Yoshita, Katsushi; Yano, Yuichiro; Ohkubo, Takayoshi; Okamura, Tomonori; Okayama, Akira; Miura, Kasuyuki
Abstract : Background: Reducing dietary salt (sodium) intake and increasing potassium intake and sodium to potassium ratio (Na/K) are crucial in preventing hypertension. However, these changes by aging have not yet been evaluated in Japanese general population. Methods: NIPPON DATA2010 is a cohort study in the participants of the National Health and Nutrition Survey of Japan in 2010, we assessed changes in dietary sodium and potassium intake from 2010 to 2020 using spot urine. Of 2, 732 participants in the 2010 survey, 667 participants (mean age 54.8 ± 8.2 years, women 59.1%) underwent spot urine measurements in both 2010 and 2020 survey. Using Tanaka formula, we estimated 24-hour salt intake (g/day) and potassium excretion (mg/day), and calculated sodium to potassium (Na/K) ratio (mmol/mmol) in spot urine for each participant. We assessed these changes from 2010 to 2020 by sex and age groups. Results: Change in estimated 24-hour salt intake from 2010 to 2020 was not a statistically significant in all groups (see table). Only estimated 24-hour potassium excretion showed a statistically significant increase in women and men ≧60 years, and the change showed a tendency towards statistical significance in men < 60 years. Na/K ratio was significantly reduced in women and men ≧60 years, not in men < 60 years. Conclusions: Potassium intake increased and dietary Na/K ratio decreased by 10-year aging in Japanese men and women, except for relatively younger men.